The Shape of the Writings. - Steinberg, Julius (Siphrut: Literature and Theology of the Hebrew Scriptures, 2015)
Intro -- Series Page -- Title -- Contents -- Preface -- Abbreviations -- The Historical Formation of the Writings in Antiquity, by Julius Steinberg and Timothy J. Stone -- Final Forms of the Writings: The Jewish and Christian Traditions, by Peter Brandt -- A Wandering Moabite: Ruth-A Book in Search of a Canonical Home, by Stephen Dempster -- Thoughts on the "Davidization" of the Psalter, by Frank-Lothar Hossfeld and Erich Zenger -- Reading Job following the Psalms, by Will Kynes -- The Place of Wisdom Literature in an Old Testament Theology: A Thematic and Structural-Canonical Approach, by Julius Steinberg -- The Search for Order: The Compilational History of Ruth, by Timothy J. Stone -- The Associative Effects of Daniel in the Writings, by Amber Warhurst -- Chronicles as the Intended Conclusion to the Old Testament Canon, by Hendrik J. Koorevaar -- Torah-Binding and Canon Closure: On the Origin and Canonical Function of the Book of Chronicles, by Georg Steins -- "A Threefold Cord Is Not Quickly Broken": Interpretation by Canonical Division in Early Judaism and Christianity, by Stephen B. Chapman -- Response, by John Barton -- Response, by Tamara Cohn Eskenazi -- Response, by Christopher R. Seitz -- Index of Authors -- Index of Scripture.